268 The mortality experience of UK workers occupationally exposed to lead. (11th October 2013) - McElvenny, M; Miller,; Sleeuwenhoek,; Van, Tongeren; Shepherd,; Cherrie,
Abstract : Objectives: Although the worldwide occurrence of lead in the environment has decreased greatly due to the elimination of most leaded petroleum, occupational exposures continue primarily via the lead battery industry and manufacture of lead pigments in paints. Around 7, 000 workers are currently under surveillance for lead exposure in Great Britain. The most recent evaluation by the International Agency for Research on Cancer working group described the evidence in humans for the carcinogenicity of inorganic lead compounds as "limited" and for organic lead compounds as "inadequate". The evidence for carcinogenicity in workers exposed to inorganic lead is most consistent for stomach cancer, with lung, kidney and brain cancer showing elevated mortality in some but not all studies. Additional studies to investigate the carcinogenicity of lead are therefore of international importance. Methods: We will present the mortality analysis of some 10, 000 workers who were included in a lead worker cohort established by the UK Health and Safety Executive (HSE) in the late 1970s/early 1980s, and which has never previously been analysed. Blood lead summaries are available for the workers, from around the time of cohort recruitment. Exposure will be characterised by these measurements and by exposure assessment groupings based on process codes and other data. Results: Individual mean blood lead levels ranged from 2 to 492 μg/dl. As well as estimating relative risks by calculating standardised mortality ratios for the range of causes of a priori interest, we will examine whether risks increase with increasing level of lead exposure. Conclusions: Many of the cohort studies carried out to date have been small and have suffered from methodological problems, but this study has the power to add substantially to the epidemiological evidence on this important issue.